1996
DOI: 10.1021/bi952822s
|View full text |Cite
|
Sign up to set email alerts
|

A Kissing Complex Together with a Stable Dimer Is Involved in the HIV-1Lai RNA Dimerization Process in Vitro

Abstract: Retroviruses contain a dimeric RNA consisting of two identical molecules of genomic RNA. The interaction between the two monomers is thought to occur near their 5'ends. We previously identified a region upstream from the splice donor site, comprising an autocomplementary sequence, responsible for the formation of dimeric HIV-1Lai RNA [Muriaux, D., Girard, P.-M., Bonnet-Mathonire, B., & Paoletti, J.(1995) J. Biol. Chem. 270,8209-8216]. This region appeared to be confined within a putative stem-loop structure. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
154
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(171 citation statements)
references
References 41 publications
16
154
1
Order By: Relevance
“…These tight dimers are defined by their resistance to dissociation during electrophoresis at room temperature and in the presence of EDTA. The tight dimer behavior of small HIV-1 or HIV-2 RNAs is thought to be caused by an extended base pairing arrangement of SL1 (first proposed in (6,33,34) and further analyzed in (10,11,15)). The 1-444 RNA is well suited to forming a tight dimer probably because the SL1 dimer-inducing element is located at the very 3′ end of this fragment ( Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…These tight dimers are defined by their resistance to dissociation during electrophoresis at room temperature and in the presence of EDTA. The tight dimer behavior of small HIV-1 or HIV-2 RNAs is thought to be caused by an extended base pairing arrangement of SL1 (first proposed in (6,33,34) and further analyzed in (10,11,15)). The 1-444 RNA is well suited to forming a tight dimer probably because the SL1 dimer-inducing element is located at the very 3′ end of this fragment ( Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…2; 3; 7; 18-20 Experiments performed in vitro have shown that the metastable KL complex can subsequently isomerize into a more stable extended duplex (ED) that involves extensive intermolecular base-pairing along the entire SL1 sequence (Scheme 1). [21][22][23][24][25] The transition between KL and ED forms is catalyzed in vitro by NC, 23; 26-29 in a process that could explain the increased thermal stability observed for genomic RNA of HIV-1 and Moloney murine leukemia virus upon protease-dependent viral maturation. 30-32 The 3D structures of SL1 constructs in monomeric, 33-35 KL, 36-40 and ED form 38; 41-43 support the two-step dimerization model.…”
Section: Introductionmentioning
confidence: 99%
“…The transient formation of an intermolecular kissing complex is required for RNA dimerization during the life cycle of retroviruses (11)(12)(13)(14)(15), and for the formation of some antisensetarget complexes (16,17). Kissing complexes in which the loop nucleotides are complementary can form stable dimers that contain intermolecular base pairs between the loop nucleotides only.…”
mentioning
confidence: 99%